2017
DOI: 10.1177/0148607116672264
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition Identified by the Academy of Nutrition and Dietetics and American Society for Parenteral and Enteral Nutrition Consensus Criteria and Other Bedside Tools Is Highly Prevalent in a Sample of Individuals Undergoing Treatment for Head and Neck Cancer

Abstract: The Academy/ASPEN Consensus and the PG-SGA were in good agreement. It is unclear whether PA and IR can be used as surrogate markers of nutrition status or muscle loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 26 publications
1
44
0
Order By: Relevance
“…Since the publication of the adult malnutrition consensus characteristics (AMC), numerous studies have been published to assess their usability and feasibility . Usability refers to the ease with which an instrument can be administered, interpreted by the participant, and scored/interpreted by the researcher .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the publication of the adult malnutrition consensus characteristics (AMC), numerous studies have been published to assess their usability and feasibility . Usability refers to the ease with which an instrument can be administered, interpreted by the participant, and scored/interpreted by the researcher .…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Mulasi et al also assessed the validity of malnutrition identification between the AMC and PG‐SGA among head and neck cancer patients (n = 19) receiving medical treatment . The study results showed a high prevalence of malnutrition (67% of subjects) prior to cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…consensus statement for the diagnosis of malnutrition which requires at least two of the following six markers to be present: unintended weight loss; loss of muscle or subcutaneous fat; fluid accumulation; insufficient energy intake; and diminished functional status using handgrip strength (White, Guenter, Jensen, Malone, & Schofield, 2012). This definition has been compared to the assessment of nutritional status using the established PatientGenerated Subjective Global Assessment tool (Ottery, 2005) and was found to be in good agreement with 94% sensitivity (Mulasi et al, 2016).…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…These patients typically are well-nourished, non-smokers, with low levels of alcohol intake, and overall have a better prognosis (Mallen-St Clair, Alani, Wang, & Srivatsan, 2016). Despite this, a recent cross-sectional study in cancer patients (n=366 with HNC) reported pre-treatment malnutrition prevalence at 49% (Hebuterne et al, 2014), and a smaller prospective longitudinal study (n=19) reported prevalence rates of 68% (Mulasi et al, 2016). Both of these rates are still high but neither of these studies provided details of HPV status.…”
Section: Head and Neck Cancermentioning
confidence: 99%
See 1 more Smart Citation